1997
DOI: 10.1159/000268008
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Timolol and UF-021 (a Prostaglandin-Related Compound) on Pulsatile Ocular Blood Flow in Normal Volunteers

Abstract: The effects of topically applied timolol (a nonselective beta-blocker) and UF-021 (a prostaglandin-related compound) on pulsatile ocular blood flow (POBF) were investigated in 9 healthy volunteers. One drop of either UF-021 or timolol was instilled in one randomly selected eye and the fellow eye received physiologic saline. Before and 90 min after drop instillation, we measured intraocular pressure (IOP), POBF, heart rate (HR) and blood pressure (BP). After a washout interval of at least 1 week, the other drug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Although we cannot with certainty rule out the possibility that the IOP lowering effect of latanoprost may account for these increases, we can point to data indicating that other mechanisms may be responsible. Previous studies have shown that a significant reduction in IOP does not necessarily result in increases in OPA and POBF (Bosem et al 1992;James 1994;Morsman et al 1995;Kitaya et al 1997).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Although we cannot with certainty rule out the possibility that the IOP lowering effect of latanoprost may account for these increases, we can point to data indicating that other mechanisms may be responsible. Previous studies have shown that a significant reduction in IOP does not necessarily result in increases in OPA and POBF (Bosem et al 1992;James 1994;Morsman et al 1995;Kitaya et al 1997).…”
Section: Discussionmentioning
confidence: 95%
“…Kitaya et al reported that Unoprostone had no effect on either IOP or POBF in healthy volunteers before and 90 minutes after instillation (Kitaya et al. 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Timolol’s influence on ocular hemodynamics remains unclear as varying results have been reported. With the OBF system, POAG patients treated for 1 month with timolol 0.5% did not have any significant pulsatile blood flow alteration; however, Kitaya et al [23]reported a significant pulsatile OBF reduction in the treated and fellow eyes of a group of healthy volunteers 90 min after timolol administration. Conversely, Grunwald [24, 25]reported an increase in retinal blood flow measured with laser Doppler velocimetry in controls and ocular hypertensives after topical administration of timolol.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we have previously shown that there is a significant negative correlation between POBF and axial length. [7][8][9] The purpose of this retrospective study was to determine whether the decreased choroidal circulation detected shortly after SB is maintained for longer periods.…”
mentioning
confidence: 99%